2010
DOI: 10.1080/10410236.2010.521916
|View full text |Cite
|
Sign up to set email alerts
|

Action Tendency Emotions Evoked by Memorable Breast Cancer Messages and Their Association With Prevention and Detection Behaviors

Abstract: Memorable messages about breast cancer sent by different sources, such as friends and family members, were analyzed for the action tendency emotions that they evoked. Negative emotions of fear, sadness, and anger, and positive emotions of hope and relief were analyzed for their associations with prevention and detection breast cancer behaviors. Messages that evoked fear were significantly more likely to be associated with detection behaviors, whereas messages that evoked relief were significantly less likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…A major contribution of our exploratory study of first sexual experiences to existing literature is the productive ways in which we investigated the narratives of memorable messages broadly defined, given the powerful ways in which they serve as a template for understanding human life (Browning, 2009). This epistemological shift away from a rational-scientific paradigm (Fisher, 1987) seen in traditional memorable message research (Knapp et al, 1981;Smith et al, 2010) provides a valuable opportunity to study memorable messages as determined by participant narratives rather than existing conceptualizations. From the perspective of students at three diverse colleges and universities, memorable first-time sexual narratives about sex were gained through personal experiences-something that appears in existing literature but is relatively unexplored (Ellis & Smith, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major contribution of our exploratory study of first sexual experiences to existing literature is the productive ways in which we investigated the narratives of memorable messages broadly defined, given the powerful ways in which they serve as a template for understanding human life (Browning, 2009). This epistemological shift away from a rational-scientific paradigm (Fisher, 1987) seen in traditional memorable message research (Knapp et al, 1981;Smith et al, 2010) provides a valuable opportunity to study memorable messages as determined by participant narratives rather than existing conceptualizations. From the perspective of students at three diverse colleges and universities, memorable first-time sexual narratives about sex were gained through personal experiences-something that appears in existing literature but is relatively unexplored (Ellis & Smith, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A message is memorable because it provides an answer to an inner conflict or personal problem, prompts a greater understanding of self, or provides a guide to self-assessment of behavior that is analyzed and discussed . While earlier research found that memorable messages were offered verbally by older people with higher statuses in comparison to the participant (Knapp et al, 1981), more recent studies identify more diverse sources of memorable message, including peers (Smith et al, 2010) and those gained from personal experiences (Ellis & Smith, 2004). Extending this work, our intended focus is to explore first sexual experiences that individuals reported as having significant impact on current sexual practices.…”
Section: The Narratology Of Memorable Messages About Relationships Anmentioning
confidence: 90%
See 1 more Smart Citation
“…The ATF links discrete emotional experiences to predictable judgments and behavioral choices due to changes in cognition, physiology, and action in response to the event that elicited the emotion (Lerner & Keltner, 2000. It is argued that emotions have direct impact on persuasion and behavior due to their associated action tendencies (Dillard & Nabi, 2006), and a growing trend surrounds the ability of certain discrete emotions to elicit predictable judgments, intentions, and behaviors (Han, Lerner, & Keltner, 2007;Lazarus, 1991;Lerner & Keltner, 2000Nabi, 2002), particularly within the health communication context (Hamel, 2014;Smith et al, 2010). However, it remains unclear what message sources are likely to elicit discrete emotions and what behavioral responses are likely to result from discrete emotional experiences.…”
Section: Action Tendency Emotionsmentioning
confidence: 98%
“…Emotion focused research suggests that the experience of discrete emotions may prompt predictable behavior (Lazarus, 1991;Nabi, 2002;Smith et al, 2010). This link between behavioral responses and discrete emotions is the foundation of a body of research on action tendency emotions and the appraisal tendency framework (ATF) (Lerner & Keltner, 2000.…”
Section: Action Tendency Emotionsmentioning
confidence: 98%